Sucrose-Sweetened Drinks Reduce the Physical Performance and Increase the Cardiovascular Risk in Physically Active Males - Raianne dos Santos Baleeiro; Aparecida Patricia Guimarães; Perciliany Martins de Souza; Rafael da Silva Andrade; Karina Barbosa de Queiroz; Daniel Barbosa Coelho; Emerson Cruz de Oliveira; Lenice Kappes Becker (Journal of Nutrition and Metabolism)
Introduction. The intake of sugar-sweetened beverages (SSBs) has increased rapidly, but the effects of this habit on health and physical performance are unknown. This study assessed the effect of excessive SSB intake on biochemical, physical performance, and biochemical and cardiovascular parameters of physically active males. Methods. Seventeen volunteers consumed a placebo drink (Pd; carbohydrate free) and an excessive SSB drink (eSSBd = Pd plus 300 g sucrose). In a blind randomized crossover study, the subjects were assigned to Pd or eSSBd groups for 15 days. After an interval of 7 days, subjects were reassigned to the other condition. Results. After eSSBd intake, there was an increase in weight (69.34 ± 13.71 vs. 70.62 ± 14.06), body mass index (24.49 ± 4.01 vs. 24.97 ± 4.13), waist circumference (75.33 ± 11.22 vs. 76.79 ± 11.51), VLDL (19.54 ± 9.50 vs. 25.52 ± 11.18), triglycerides (78.94 ± 23.79 vs. 114.77 ± 43.65), and peak systolic blood pressure (178.57 ± 26.56 vs. 200.71 ± 24.64). The cardiorespiratory response to exercise (VO2max) (48.15 ± 10.42 vs. 40.98 ± 11.20), peak heart rate (186.64 ± 8.00 vs. 179.64 ± 6.28), total exercise time (15.02 ± 1.57 vs. 14.00 ± 2.18), and mechanical work (15.83 ± 4.53 vs. 13.68 ± 5.67) decreased after eSSBd intake (all values expressed in initial mean ± DP vs. final). The rates of perceived exertion were higher (1.300 vs.1.661 slope and −0.7186 vs. −1.118 y-intercept) after eSSBd intake. Conclusion. The present study shows that 15 days of eSSBd intake may negatively modulate biochemical parameters associated with cardiovascular risk. In addition, this overintake can impair the physical performance and cardiovascular responses to physical exercise.